Breeding habitat of poorly studied humpback whales (Megaptera novaeangliae) in Boa Vista, Cape Verde - Ryan, Conor; Craig, Darren; Lopez-Suarez, Pedro; Vazquez Perez, Jose; O'Connor , Ian; Berrow, Simon D. (J. Cetacean Res. Manage., 2023)
The waters surrounding Cape Verde comprise one of two known breeding grounds for humpback whales in the North Atlantic. The population remains very small and has apparently failed to recover since the cessation of whaling there. During the breeding seasons of 2011 and 2012, sighting surveys were carried out for humpback whales off Boa Vista, the easternmost island of the Cape Verde Island archipelago. The distribution and relative abundance of humpback whales and mother-calf pairs was investigated by plotting effort-corrected sightings using a 2km2 grid-square. The study area, a 206km2 region from the coastline up to 8km offshore, covered the western half of Boa Vista where whales have previously been regularly recorded. Following 1,954km of search effort, 117 sightings of humpback whales were made. An encounter rate of 0.11 whales per km was recorded for both years. It is hoped that these data may assist in implementing conservation measures to protect humpback whales and the habitat of Baia Sal Rei, which appears to be the single most important bay for winter breeding, calving and nursing humpback whales in the eastern North Atlantic.